(untitled) (Medical Forum Monthly, 2024)
Mucormycosis is rare, life threatening infection, especially in diabetic with ketoacidosis. The infection is caused by a group of saprophytic fungi of class phycomicetes rhizomucor, rhizopus and mucor are more common fungi. The diagnosis is based on high clinical suspicion, CT / MRI imaging and histopathological confirmation. We present a 50 years, diabetic female, with history of mainly left sided facial pain, swelling is recent decreased left eye movement as well. High suspicion of Mucormycosis on CT which confirmed on histopathology later on. Patient responded well clinically with amphotericine B posaconazole & endoscopic debridement. Patient was discharged 10 days later with followed up MRI and antifungal treatment for 6 month.